2010
DOI: 10.1080/15363831003783005
|View full text |Cite
|
Sign up to set email alerts
|

The Studies of Equilibrium and Thermodynamic Adsorption of Pb(II), Cd(II) and Cu(II) Ions from Aqueous Solution onto SWCNTs and SWCNT–COOH Surfaces

Abstract: The equilibrium and thermodynamics of Pb(II), Cd(II) and Cu(II) ions adsorption from aqueous solution onto single-walled carbon nanotube (SWCNT) and carboxylate group functionalized single-walled carbon nanotube (SWCNT-COOH) surfaces were studied by atomic absorption spectroscopy. The effect of contact time, pH, initial concentration of ion, ionic strength and temperature on the adsorption of ion was investigated. The results indicated that Langmuir model fits adsorption isotherm data better than the Freundlic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…Based on our simulations, the adsorption capacity of divalent metal ions in the presence of the COOfunctional group on the CNT is higher due to the presence of additional oxygen binding site.Hence, the adsorption capacity of all the metal ions (Cd 2+ , Cu 2+ , Pb 2+ and Hg 2+ ) on functionalized CNT-COO -(seeFigure 8) is higher than that seen in the presence of other functional groups (-OH and -CONH 2 ) and bare CNT. The total amount adsorption (q m ) of metal ion on CNT surface at equilibrium will saturate with increase in the initial concentration (C 0 ) of metal ion, as observed in various experimental works 1,20,32. However, the relative amount of adsorption ∆C/C 0 will decrease with the increase in concentration (C 0 ) of metal ion in the…”
mentioning
confidence: 82%
“…Based on our simulations, the adsorption capacity of divalent metal ions in the presence of the COOfunctional group on the CNT is higher due to the presence of additional oxygen binding site.Hence, the adsorption capacity of all the metal ions (Cd 2+ , Cu 2+ , Pb 2+ and Hg 2+ ) on functionalized CNT-COO -(seeFigure 8) is higher than that seen in the presence of other functional groups (-OH and -CONH 2 ) and bare CNT. The total amount adsorption (q m ) of metal ion on CNT surface at equilibrium will saturate with increase in the initial concentration (C 0 ) of metal ion, as observed in various experimental works 1,20,32. However, the relative amount of adsorption ∆C/C 0 will decrease with the increase in concentration (C 0 ) of metal ion in the…”
mentioning
confidence: 82%
“…Those of ox-MWCNT were best in the pH range of 6-10 whereas Cd(II) sorption was only slightly dependant on pH for as-grown MWCNT. Adsorption on to all HNO 3 or NaOCl or KMnO 4 Scheme 1 Mechanism of adsorption of divalent metal ions on to SWCNT-COOH [39] (With permission from Moradi et al [39]) three types of CNT increased rapidly with contact time (30 min for equilibrium to be achieved). They also found that affinity for Cd(II) from aqueous solutions was greater for e-MWCNT than for ox-MWCNT and as-grown MWCNT.…”
Section: Functionalised Cntmentioning
confidence: 97%
“…Moradi et al [39] compared the adsorption of Pb(II), Cd(II), and Cu(II) from aqueous solutions on to SWCNT and SWCNT-COOH (Scheme 1). Adsorption capacities of SWCNT-COOH for Pb(II), Cu(II), and Cd(II) were 96.02, 77.00, and 55.89 mg/g, respectively.…”
Section: Oxidised Cntmentioning
confidence: 99%
“…Various thermodynamic parameters (standard Gibbs free energy, standard enthalpy, and entropy) were calculated by equations (10-12): (10) (11) (12) ...where K C is the equilibrium constant, T is the absolute temperature (K), and R is the universal gas constant (8.314 J/mol·K) [41]. ΔHº and ΔSº were calculated from the slope and intercept of the plot of LnK C vs. 1/T using equation 12 (Fig.…”
Section: Adsorption Thermodynamic Studiesmentioning
confidence: 99%